New accessions of tomato resistant to whitefly biotype B - Fernandes, Maria Elisa de Sena; Silva, Derly José Henriques da; Fernandes, Flávio Lemes; Picanço, Marcelo Coutinho; Gontijo, Pabro Costa; Galdino, Tarcísio Visintim da Silva (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate resistance to Bemisia tabaci biotype B in 34 tomato (Lycopersicon esculentum) accessions from the Banco de Germoplasma de Hortaliças of UFV. The number of adults, eggs and nymphs per plant besides of trichome density were evaluated. Differences between accessions were found for the evaluated variables. Accessions BGH-166, BGH-616, BGH-850, BGH-990, BGH-2102 and BGH-2125 presented less infestation of adults, eggs and nymphs per plant and showed lower trichome density. The resistance of these tomato accessions to whitefly was associated to a lower trichome density.